Therapeutic Outcomes And Mortality Related To Hemodialysis Among Hospitalized Hypertensive And Diabetic Patients In Jakarta, Indonesia And Penang, Malaysia - Ramatillah, Diana Laila (2018)
Therapeutic outcomes of hemodialysed patients usually depend on proper pharmacotherapy given and follow up of the patients. Based on the high mortality incidence of this category, a study was conducted in both countries, Indonesia and Malaysia. A total of 455 patients from HD center Jakarta and Penang were included in this study based on inclusion and exclusion criteria. A retrospective evaluation of 199 patients in both countries were also included. All patients that fulfilled the criteria were included in HD center Penang and Jakarta as convenience sampling. In 256 hemodialysed patients who were evaluated by prospective, 14.8 % had diabetes mellitus, 55.1% had hypertension and 30.1 % had diabetes mellitus and hypertension.